Using compaction simulation experiment to recover burial history: Taking the fourth Member of Shahejie Formation in Leijia area, Western Depression of Liaohe River as an example - Xiaoyang Zhao; Zongyang Dai; Yang Li; Yubo Jiang; Zhenchao Gong; Tian Li; Lan Huang; Xiaolei Cui; Rui Zhou; Jing Su; Lei Huang; Xiaolong Zhou (地质科技通报, 2021)
The Leijia area in the Western Depression of the Liaohe River has good oil and gas exploration and development potential, but the current analysis of the burial history in this area lacks a clear understanding.This paper uses the recovery principle of subsidence history to restore the original thickness of the remaining stratum in the study area.Firstly, the sonic curve method and the adjacent layer comparison method are used to restore the denuded thickness of the stratum.Sandstone, argillaceous limestone, limestone mudstone, mudstone) were subjected to compaction simulation experiments, and the porosity-depth curve of the sample was obtained according to the experiment.Use the existing burial data to calculate the thickness of the stratum framework, and according to the constant volume formula of the framework, use each single lithological layer as the smallest unit to carry out the backstripping calculation one by one to obtain the sedimentary thickness of each group and section in different geological periods and the depth of burial.According to the analysis of burial history, during the burial process of the Cenozoic strata in Leijia area, the sedimentation rate of the Paleogene Shahejie Formation was higher and the sedimentary strata was thicker, but the second Member of Shahejie Formation was uplifted and eroded and the strata was thin; During the Dongying Formation, the stratum deposition slowed down, and the stratum was uplifted and eroded at the end; in the Neogene and Quaternary, the stratum deposition rate was low, and the thickness of the deposited stratum was not large.